2011
DOI: 10.1128/jcm.02564-10
|View full text |Cite
|
Sign up to set email alerts
|

HIV Coreceptor Tropism in Paired Plasma, Peripheral Blood Mononuclear Cell, and Cerebrospinal Fluid Isolates from Antiretroviral-Naïve Subjects

Abstract: A survey of HIV coreceptor usage in cerebrospinal fluid (CSF) samples, peripheral blood mononuclear cells (PBMCs), and plasma samples from naïve seropositive patients was conducted. One hundred patients were enrolled in this study. Of the 100 patients, 36 had a primary or recent infection (P-RI), 31 had an early chronic infection (>350 CD4 cells) (ECI), and 33 had a late chronic infection (LCI). All 3 compartments were sampled in a subset of 33 participants, while the remaining 67 patients provided plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
(51 reference statements)
2
24
0
1
Order By: Relevance
“…(16). Our observations are in agreement with three studies on 38, 34, and 100 patients, which also showed high concordances (82% to 90%) between plasma and PBMC samples (18,23,24). The observed high concordances between HIV RNA and HIV DNA assessments may indicate that HIV DNA-derived tropisms also by and large reflect the major HIV tropism within a patient.…”
supporting
confidence: 91%
“…(16). Our observations are in agreement with three studies on 38, 34, and 100 patients, which also showed high concordances (82% to 90%) between plasma and PBMC samples (18,23,24). The observed high concordances between HIV RNA and HIV DNA assessments may indicate that HIV DNA-derived tropisms also by and large reflect the major HIV tropism within a patient.…”
supporting
confidence: 91%
“…As systemic infection progresses, CSF viruses may show more diverse compartmentalization involving R5 viruses that infect macrophages and related cells (referred to as M-tropic) [24][25][26][27][28][29]. While full formal proof of this remains to be shown, it is likely that these viruses are important in the development of encephalitis, in which productive infection can be identified in perivascular and parenchymal macrophages and microglial cells [30].…”
Section: Cns Hiv Infection and Treatment Effectsmentioning
confidence: 99%
“…For plasma RNA samples, G2P was set at a false-positive rate (FPR) of 10%, according to guidelines on the clinical management of HIV-1 tropism testing (8). For pvDNA samples, G2P was set at FPR values of both 10%, as reported in several studies (2,11,18,26,27), and 20%, as recommended by guidelines (8). Thus, sequences with FPRs of Ͻ10% from both plasma RNA and pvDNA samples and Ͻ20% from pvDNA samples were considered X4/dualmixed tropic.…”
Section: Methodsmentioning
confidence: 99%